2011
DOI: 10.5301/ejo.5000069
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids in Age-Related Maculopathy Italian Study (CARMIS): Two-Year Results of a Randomized Study

Abstract: Patients treated with lutein/zeaxanthin and astaxanthin together with other nutrients were more likely to report clinically meaningful stabilization/improvements in VA, CS, and visual function through 24 months compared with nontreated subjects. Further studies are needed with more patients and for longer periods of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 22 publications
3
52
0
1
Order By: Relevance
“…Of note, concentrations of L are higher in the peripheral macula, compared with the foveola. 56 Previous studies have investigated the impact of macular carotenoid supplementation on CS in subjects with AMD, with most of the studies reporting improvements in the CS after supplementation (with L and Z), 36,37,[57][58][59] although no study to date has tested 60 has shown significant increases in CS at low spatial frequencies after supplementation with either 10 mg L, 20 mg L, or 10 mg L and 10 mg Z (combined), in subjects with early AMD, over a 48-week study period. These findings are in agreement with those reported in this study, which found demonstrable improvements in CS at high spatial frequencies, but only among subjects who were supplemented with a formulation containing MZ, and not among subjects supplementing with high doses of L alone.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, concentrations of L are higher in the peripheral macula, compared with the foveola. 56 Previous studies have investigated the impact of macular carotenoid supplementation on CS in subjects with AMD, with most of the studies reporting improvements in the CS after supplementation (with L and Z), 36,37,[57][58][59] although no study to date has tested 60 has shown significant increases in CS at low spatial frequencies after supplementation with either 10 mg L, 20 mg L, or 10 mg L and 10 mg Z (combined), in subjects with early AMD, over a 48-week study period. These findings are in agreement with those reported in this study, which found demonstrable improvements in CS at high spatial frequencies, but only among subjects who were supplemented with a formulation containing MZ, and not among subjects supplementing with high doses of L alone.…”
Section: Discussionmentioning
confidence: 99%
“…Results of some but not all intervention studies (1, 11, 115, 133, 135, 187, 192) indicate improvements in visual acuity when L and/or Z are supplemented alone (77, 113, 139) or, more often, in conjunction with other antioxidants and/or omega-3 fatty acids (1, 12, 43, 49, 147, 155). Three of seven randomized trials in >50 individuals with early or advanced AMD (116, 156) or with diabetic retinopathy (77) indicate improvements in visual acuity.…”
Section: Roles In Visual Healthmentioning
confidence: 99%
“…This low consumption of fruit and vegetables may result in low intakes of fat-soluble, health-promoting, bioactive compounds such as carotenoids from these foods (2). Dietary carotenoids have beneficial biological properties including antioxidant and antiinflammatory effects, and research has supported the potential for protective effects of carotenoids against many degenerative diseases, including cardiovascular diseases, age-related macular degeneration, and some types of cancer (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%